Gut microbiota and oral cavity cancer: a two-sample bidirectional Mendelian randomization study - Sun, Zhijuan; Bai, Chunying; Hao, Dandan; Jiang, Xiling; Chen, Jianxing (Frontiers in Oncology, 2024)
This study employs a two-sample bidirectional Mendelian randomization (MR) approach to systematically evaluate the causal relationship between gut microbiota and oral cavity cancer (OCC). Objective: To address the challenge in establishing the causal relationship between gut microbiota and OCC, we applied a systematic MR analysis. Methods: Utilizing GWAS data from the MiBioGen consortium (18,340 individuals) and UK Biobank (n = 264,137), we selected instrumental variables and employed MR-Egger, weighted median, IVW, and weighted mode analyses. Heterogeneity and pleiotropy were assessed using Cochran's Q test and MR-Egger intercept test. Results: Our findings indicate, at the order level, Bacteroidales (OR = 0.9990, 95% CI = 0.9980-1.0000, P = 0.046), Burkholderiales (OR = 1.0009, 95% CI = 1.0001-1.0018, P = 0.033), and Victivallales (OR = 0.9979, 95% CI = 0.9962-0.9995, P = 0.037) exhibit causality on OCC in the Weighted median, IVW, and MR-Egger analyses, respectively. At the family level, Alcaligenaceae (OR = 1.0012, 95% CI = 1.0004-1.0019, P = 0.002) and Clostridiaceae1 (OR = 0.9970, 95% CI = 0.9948-0.9992, P = 0.027) show causality on OCC in IVW and MR-Egger analyses. At the genus level, Clostridiumsensustricto1 (IVW, OR = 0.9987, 95% CI = 0.9980-0.9995, P = 0.001; MR-Egger, OR = 0.9978, 95% CI = 0.9962-0.9995, P = 0.035), Desulfovibrio (IVW, OR = 1.0008, 95% CI = 1.0001-1.0015, P = 0.016), Eggerthella (IVW, OR = 0.9995, 95% CI = 0.9990-1.0000, P = 0.048), Eubacterium fissicatena group (IVW, OR = 1.0005, 95% CI = 1.0000-1.0009, P = 0.032), and Holdemanella (IVW, OR = 0.9994, 95% CI = 0.9989-0.9999, P = 0.018) are implicated in causing OCC in related analyses. Conclusions: Our study identifies Burkholderiales order, Alcaligenaceae family, Desulfovibrio genus, and Eubacterium fissicatena group as causally increasing OCC risk. In contrast, Bacteroidales order, Victivallales order, Clostridiaceae1 family, Clostridiumsensustricto1 genus, Eggerthella genus, and Holdemanella genus are causally associated with a decreased OCC risk. However, further investigations are essential to delineate an optimal gut microbiota composition and unravel the underlying mechanisms of specific bacterial taxa in OCC pathophysiology.